2015
DOI: 10.5146/tjpath.2015.01328
|View full text |Cite
|
Sign up to set email alerts
|

The role of frozen-section in the surgical management of patients with endometrial intraepithelial neoplasia

Abstract: Objective: Patients with endometrial intraepithelial neoplasia may have concurrent endometrial cancer if managed surgically or develop cancer in time if managed conservatively. Therefore, intraoperative assessment of the uterus may be helpful if a surgical approach is decided on. Our study aimed to investigate the role of frozen-section examination in patients with endometrial intraepithelial neoplasia. Material and Method:Patients with endometrial intraepithelial neoplasia who were subjected to hysterectomy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The results of the scoping review were reported according to the Preferred Reporting Items for Systematic reviews and Meta-criteria and were included in our review. We included 24 primary studies, [9][10][11][13][14][15][16][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] three meta-analyses, [17][18][19] and one poster presentation. 12 The characteristics of the 28 included studies are shown in Table 2.…”
Section: Stage 5: Summarizing Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the scoping review were reported according to the Preferred Reporting Items for Systematic reviews and Meta-criteria and were included in our review. We included 24 primary studies, [9][10][11][13][14][15][16][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] three meta-analyses, [17][18][19] and one poster presentation. 12 The characteristics of the 28 included studies are shown in Table 2.…”
Section: Stage 5: Summarizing Resultsmentioning
confidence: 99%
“…12 The characteristics of the 28 included studies are shown in Table 2. Five studies were multicentric, 17-19, 27,35 five studies were from Turkey, 11,15,20,23,25 four studies were from the USA, 12,13,21,22 two studies were from the UK, 14,16 two studies were from Canada 10,34 and there was one study from each of Australia, 9 South Korea, 24 France, 26 Belgium, 28 Italy, 29 Denmark, 30 Greece, 31 Norway, 32 Taiwan, 33 and China. 36 These studies included the data of 7409 patients and recorded 2377 concurrent EC cases (32.1%).…”
Section: Stage 5: Summarizing Resultsmentioning
confidence: 99%
See 3 more Smart Citations